2020
DOI: 10.1002/anie.201915650
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Layered P2@P3 Integrated Spinel Structure Evolution for High‐Performance Sodium‐Ion Batteries

Abstract: Structural evolution of the cathode during cycling plays a vital role in the electrochemical performance of sodium‐ion batteries. A strategy based on engineering the crystal structure coupled with chemical substitution led to the design of the layered P2@P3 integrated spinel oxide cathode Na0.5Ni0.1Co0.15Mn0.65Mg0.1O2, which shows excellent sodium‐ion half/full battery performance. Combined analyses involving scanning transmission electron microscopy with atomic resolution as well as in situ synchrotron‐based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 27 publications
1
66
0
Order By: Relevance
“…Recently, engineering P2/P3 biphases in layered oxides has been reported as an effective strategy for improving the electrochemical performance due to the synergistic effect between phases. [ 12,16–23 ] For example, Guo and co‐workers [ 16 ] demonstrated that the crystalline structure of P2/P3–Na 0.7 Li 0.06 Mg 0.06 Ni 0.22 Mn 0.67 O 2 cathode combines the respective advantages of P2 and P3 phases, and thus exhibits enhanced long‐term cycling performance over 100 cycles and rate capability (≈102 mA h g −1 at 5 C) compared with the pure P2 or P3 phase. Ionic substitution is a feasible method to manipulate the phase composition of Na x MnO 2 layered oxides.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, engineering P2/P3 biphases in layered oxides has been reported as an effective strategy for improving the electrochemical performance due to the synergistic effect between phases. [ 12,16–23 ] For example, Guo and co‐workers [ 16 ] demonstrated that the crystalline structure of P2/P3–Na 0.7 Li 0.06 Mg 0.06 Ni 0.22 Mn 0.67 O 2 cathode combines the respective advantages of P2 and P3 phases, and thus exhibits enhanced long‐term cycling performance over 100 cycles and rate capability (≈102 mA h g −1 at 5 C) compared with the pure P2 or P3 phase. Ionic substitution is a feasible method to manipulate the phase composition of Na x MnO 2 layered oxides.…”
Section: Figurementioning
confidence: 99%
“…[ 12,20,22 ] Dou and co‐workers [ 12 ] employed Zn substitution to synthesize P2/P3 intergrowth composite, which exhibits improved structural stability and humidity resistance. Chou and co‐workers [ 22 ] demonstrated that Mg can manipulate the phase components and designed P2/P3 integrated spinel Na 0.5 Ni 0.1 Co 0.15 Mn 0.65 Mg 0.1 O 2 cathode for advanced SIBs. To the best of our knowledge, utilization of Co substitution to tune the phase composition in Na x MnO 2 has been scarcely explored so far.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] However, because of the larger ionic radius, higher reduction potential, and slower reaction kinetics of Na + ions compared to Li + ions, exploring electrodes with high reversible capacities and facile reaction processes remains challenging. [5][6][7][8] In the past few years, a wide range of promising materials has been developed as efficient electrode materials for SIBs, including cathode materials (e.g., polyanions, [9][10][11][12] transition metal oxides, [13][14][15][16][17] hexacyanoferrates [18,19] ) and anode materials (e.g., alloys, [20][21][22][23][24][25][26] metal chalcogenides, [27][28][29][30][31][32] carbonaceous materials [33][34][35] ). It is noteworthy that the electrodes with two/multiple-electron reactions are more favored because of the high theoretical capacity for energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the P sites prefer to attract the protons in the electrolyte, contributing to a suitable bonding between the catalytic sites and the intermediates/products. In addition, researches about phosphides for electrocatalytic oxygen reactions have been also reported recently, extending the applications of phosphides in energy conversion [96][97][98][99][100]. Tuning the crystal structure via the strain effect has been proved to be an effective way to improve the activity.…”
Section: Transition Metal Phosphidesmentioning
confidence: 99%